2014
DOI: 10.1007/s12035-014-8992-2
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transient Receptor Potential Vanilloid 4 is Involved in Neuronal Injury in Middle Cerebral Artery Occlusion in Mice

Abstract: Transient receptor potential vanilloid 4 (TRPV4) is widely expressed in the central nervous system and can be activated by multiple stimuli during cerebral ischemia. Recently, we reported that intracerebroventricular (icv.) injection of HC-067047, a specific TRPV4 antagonist, reduced brain infarction following 60-min of middle cerebral artery occlusion (MCAO). This study was undertaken to investigate the molecular mechanisms underlying TRPV4-mediated neuronal injury in cerebral ischemia. We demonstrated that T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 37 publications
8
81
0
Order By: Relevance
“…In our previous studies, chronic activation of TRPV4 may change the expression of voltage-gated sodium channels and glutamate receptors [5, 37]. Here, hippocampal protein levels of GlyR α1, α2, α3 and β subunits were examined in GSK1016790A-injected mice.…”
Section: Resultsmentioning
confidence: 97%
“…In our previous studies, chronic activation of TRPV4 may change the expression of voltage-gated sodium channels and glutamate receptors [5, 37]. Here, hippocampal protein levels of GlyR α1, α2, α3 and β subunits were examined in GSK1016790A-injected mice.…”
Section: Resultsmentioning
confidence: 97%
“…Previous reports from our group showed that activation of TRPV4 reduced the phosphorylation of Akt (Jie et al, 2015, 2016; Hong et al, 2016). AMPK is a serine/threonine kinase that functions as an important sensor in energy homeostasis in mammalian cells.…”
Section: Discussionmentioning
confidence: 70%
“…GSK1016790A is a synthetic agonist of TRPV4 and has been used to activate TRPV4 both in vivo and in vitro (Vincent and Duncton, 2011; Jie et al, 2015, 2016; Hong et al, 2016). AICAR is a commonly used and specific activator of AMPK, and compound C (CC) is a specific antagonist of AMPK (Han et al, 2005; Venna et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations